Quality Analysis of Cloth Masks: Study of Material Types on Physical, Chemical, and Antibacterial Properties - Sayekti Wahyuningsih; Ari Handono Ramelan; Selfi Handayani; Nanang Wiyono; Sentot Budi Rahardjo; Agus Supriyanto; Windy Ayu Lestari; Retno Hartati; Rahmat Hidayat (Universitas Islam Indonesia, 2023)
Utilizing personal protective equipment (PPE) is the important requirement for controlling and preventing of Covid-19 virus spread. The awareness of mask-wearing among the citizen and the development of fabric mask testing methods based on Indonesian Standards through the implementation of SNI 7648: Textile – Test of the air permeability on fabric; SNI 20743: The evaluating method of antibacterial properties using biological aerosol S. aureus and E. coli; SNI/ISO 4920: The surface wetness testing. This study shows that we need to understand and choose fabric masks correctlybesides being standardized. Fabric types influence the performance of the mask while protecting the user.